A teoria da computação de Alan Turing - Bispo, Danilo Gustavo (2018)
The present work aims to expose the study of some aspects that permeated the emergence of Computing Theory of Alan Mathison Turing at the beginning of the 20th century. According to previous research, it is suggested that this occurred in part, due to a theoretical consequence of the development of mathematics. At the end of the nineteenth century there was an effort expended by some thinkers whose aim was to clarify the nature of truth in mathematics, a problem put in sharp evidence by the turbulent stage in the development of mathematical thinking between about 1870 and 1940 with the emergence of new types of geometry. This stage can also be interpreted as "the crisis of fundamentals" and visualized as the outcome of the development phase corresponding to the emergence of contemporary science. Within this context, the idea will now be to broaden the research to identify details of the projects that were not successful but that also had their contribution or influenced in some way the emergence of the theory that established key concepts for the digital computer model